PROFIL USAHA AGROINDUSTRI â€œKUE BEPANGâ€ DI KECAMATAN REMBOKEN - Putra P. Koagouw; Ventje V. Rantung; Olly E. Laoh; Ribka M. Kumaat (Universitas Sam Ratulangi, 2014)
ABSTRACTPutra Pratama Koagouw. The Profile of â€œBepang Cookiesâ€ Agroindustry Enterprise inRemboken Sub Distrikâ€. Under the Guidance of Prof.Dr.Ir. Ventje V. Rantung, MA. asChairman, Dr.Ir. O. Esry H. Laoh, MS. and Ir. Ribka M. Kumaat, MS. as Members.The object of this reaserch is to determine the profile of enterprise â€œBepang Cookiesâ€where its manufacturing process is simple. The location was taken by using purposivesampling method. Three families businesses as respondents scattered in three villages in thisdistrict. All three businesses have been observed from routine production activities on aweekly basis. The business were selected to represent the three villages. The primary datawere obtained from the interviews with the owners. The data collected were in the form ofcharacteristic entrepreneurs / manufacturers, raw materials, cost of production, marketing,capital, technology, management and profits.The results showed that enterprises was started by the family since the 70s with rawrice, sugar, cooking oil and plastics auxiliary materials, candles, kerosene and firewood. Theprocess was very simple with tools homemade production, performed by skilled workersaround 3-5 persons. The cost of equity capital was an average of Rp. 6.289.011,77. millionper month. By using a simple management system in which the supply of equipment andmaterials to distribution was controlled by the family, though marketing has reached fivecounties in the province. From this effort the entrepreneur gained about Rp. 5.610.988,23.million per month.It is better for the product pack to put the mark, the time limit consumption ofproducts, compositions and information without preservatives and weight (g) of the product,in order to be recognized by the consumers (market). Product marketing area can beexpanded to reach all levels of society, as well as the needed to increase or improve the shapeand variation in order to be more appealing tastes and interests of consumers. Also it canraise the volume of production that gets bigger profit.